Biomonitoramento toxicogenético como indicador de risco à saúde por exposição ao urânio de residentes que habitam as proximidades da maior reserva de urânio do Brasil, no município de Santa Quitéria – Ceará - Rodrigues, Felipe Augusto Rocha (2015)
Uranium is represented in the periodic table by the letter U, being the fourth element of the actinide group. Brazil, according to INB official data, has one of the largest reserves of uranium in the world. Uranium ionizing radiation can interfere with cellular functions at all levels of cell organization, inducing chemical and radiological toxicities. Its effect on the body is cumulative, and the radiation thus exposed can affect the DNA, inducing the development of neoplasias, such as leukemias. Therefore, biomonitoring of individuals exposed to radiation is reported in the literature as essential for human monitoring. Ceará has one of the largest uranium reserves in Brazil; The Uranium deposit of Santa Quitéria. The objective of the present work is to evaluate the possible genotoxic and mutagenic effects of human exposure to uranium in the Municipality of Santa Quiteria, using Alkaline Comet Assay techniques in human lymphocytes, Micronuclei in lymphocytes, oral mucosa and human reticulocytes, Chromosomal Aberrations In human lymphocytes and protein oxidation measurement. The samples collected totaled 161 individuals, of whom 91 were residents and 70 were non-residents. The mean age of the resident population was 41.24 ± 15.00; With an exposure time of 34.93 ± 16.06. In the alkaline comet analysis, there was a statistically significant difference between the Residual and Non Resident Population Damage Indices (IDs) of 10.63 ± 0.61 and 6.34 ± 0.31, respectively. Significant differences were found when the enzymes FPG, ENDO III, hOGG1 were used in the comet test. The highest rates were found among smokers and / or alcohol users. The results of the mutagenic evaluation, with the MN test on lymphocytes, MN on reticulocytes and MN on buccal mucosa revealed that there were no significant differences between the resident and non-resident groups. However, significant differences were found among smokers and / or alcohol users. The results of chromosomal aberrations of the resident population reveal that the frequencies of chromosomal aberrations (chromosomal and chromic breaks) of the resident population groups were significantly different when compared to the non-resident population groups. There were no differences in the results of numerical aberrations and mitotic index. Residual protein oxidation measurements showed that the dosage of carbonylated protein was significantly higher when compared to the non-resident group with the resident. The highest dosages were found among smokers and / or alcohol users. It is concluded that the uranium present in the geographic region is not enough to induce breaks in the DNA molecule, interfere with the assembly of the spindle fibers and impede the progression of the cell cycle, which should reflect the low doses of radiation to which they are exposed. Lesions in DNA as well as chromosomal changes observed in exposed smokers may be due to the effect of smoking.